Out-of-school children and the role of social reconstructionism in education in the context of Cambodia: an implication for reform policy - Yem Bunthorn (Quality Education for All)
Purpose – This study aims to explore the factors contributing to the out-of-school children (OOSC) issue at the primary level in Cambodia and related initiatives in addressing the challenges, drawing upon the application of social reconstructionism in addressing the issue. Design/methodology/approach – This paper reviews and analyzes relevant, existing literature, including scholarly articles, reports, policy documents and books. Findings – Despite efforts by the government, Ministry of Education, Youth and Sport and non-government organizations, the issue of OOSC remains a challenge. Integration of social reconstructionist principles offers a transformative approach to address the OOSC issue, as well as systemic educational disparities. Research limitations/implications – This review paper lacks empirical findings of its own and relies solely on the availability and quality of the relevant sources, setting direction for future research to explore empirical findings. Practical implications – The findings underscore the importance of adopting a holistic and socially conscious approach to education, incorporating social reconstructionist principles in reform policy. Social implications – Addressing the OOSC in Cambodia is crucial for promoting social equity and breaking the cycle of poverty, highlighting the need for inclusive education policies. Originality/value – This study contributes to the existing literature and builds upon it to offer a novel perspective of applying social reconstructionist principles in reform policy to address the OOSC issue, as well as the potential of a transformative approach to dealing with systematic educational disparities.